(الإمام الترمذي وجهوده في علم الجرح والتعديل (تطبيقاً على كتابه الجامع الصحيح - Gasmelsid, Saadeldin Mansour; Azhari, Muhammad Saiful Islam (Sudan University of Science and Technology (SUST), 2017)
Imam al-Tirmidhe one of the retainers who has contribution in the field of impugnment and validation of al-hadith. narrators. This research aims to mention the remarkable place of Imamal- Tirmidhein (Al-jarh wa al-taadel). and the superiority of his (al-jamie).The researchers came up with some conclusions. The most important outcome is that Imam al-Tirmidhe is one of them who is followed in the field of al-hadeth and its sciences. Therefore. the scholars of al-hadeth gave value for his assessment. We can find his book (al-jamie) as a main source for impugnment and validation (Al-jarh wa al-taadel) of al-hadÊth. narrators according to his own assessment. His (al-jamie) is the third position in the six books of al-hadeth. Moreover. this view: (do not rely on his purification for(al-hadeth) is not satisfactory from its narrator. The Scholars of al-hadeth rely on the opinion of Imamal-Tirmidhe